The Influence of Brand Ambassador, Live Streaming, and Price Perception on Consumers’ Repurchase Intention for Scarlett Whitening Products on the Shopee Marketplace in Pontianak City - Diva Audia Tania; Muhammad Ebuziyya Alif Ramadhan; Gun Mayudi (SAINTIS Publishing, 2026)
This study aims to analyze the influence of brand ambassador, live streaming, and price perception on consumers’ repurchase intention for Scarlett Whitening products on the Shopee marketplace in Pontianak City. The approach used is quantitative with an associative research design. Primary data were collected through the distribution of questionnaires to 100 respondents who met the purposive sampling criteria, along with brief interviews as supporting data. Secondary data were obtained from e-commerce trend reports, beauty market data, Scarlett product popularity, and information regarding brand ambassador activities and Shopee Live. The research instrument was proven valid, with all items having an r-count value above 0.196, and reliable with Cronbach’s Alpha values ranging from 0.815 to 0.855. The results of the regression analysis indicate that brand ambassador, live streaming, and price perception have a positive and significant influence on repurchase intention. Simultaneously, the three variables show a significant influence (F = 33.470; p = 0.000) with a contribution of 51.1 percent to the variation in repurchase intention (R² = 0.511). These findings strengthen the evidence that the presence of a global brand ambassador, the intensity of live streaming, and a positive price perception play important roles in shaping consumers’ repeat purchase decisions. This study provides strategic implications for local beauty brands to optimize digital marketing communication in a more integrated and sustainable manner.